PEMETAAN LITERATUR SUSTAINABLE PROPERTY : ANALISIS BIBLIOMETRIK - Sudharma, I Wayan Priyana Agus; Pradnyadewi T, Diah (Nusantara Hasana Journal, 2024)
Sustainable Property refers to the construction of property that is intended to have minimal negative impact on the environment. This has led to pressure to build structures and environments that reduce negative impacts on the environment while encouraging resource conservation, energy efficiency, and the creation of a healthy living environment. The purpose of this study is to map the development of research on Sustainable Property. The study was conducted using the Crossref database from 1970 to 2024. The results of the study show that an article by Arun Agrawal published in 2001 entitled "Common Property Institutions and Sustainable Governance of Resources" has the highest number of citations, namely 1,125. There are five clusters of publication keywords that have the most occurrences, namely intellectual property, sustainable development, practices, buildings, and investment.